2022
DOI: 10.3389/fnagi.2022.831910
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α (G-308A) Polymorphism, Circulating Levels of TNF-α and IGF-1: Risk Factors for Ischemic Stroke—An Updated Meta-Analysis

Abstract: ObjectiveAccumulated studies have explored gene polymorphisms and circulating levels of tumor necrosis factor (TNF)-α and insulin-like growth factor (IGF)-1 in the etiology of ischemic stroke (IS). Of the numerous etiopathological factors for IS, a single-nucleotide polymorphism (SNP) rs1800629 located in the TNF-α gene promoter region and increased levels of TNF-α were found to be associated with IS in different ethnic backgrounds. However, the published results are inconsistent and inconclusive. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…The optimal time point needs to be explored. Second, our study lacked some information at the time of participants' blood sample collection, including indicators of the acute inflammatory state (i.e., CRP, IL-1, IL-6, and TNF- α ) [ 29 31 ], some other drugs use such as the use of steroids and nonsteroidal anti-inflammatory drugs, previous use of antibiotics and therapy durations, and information about other diseases that could cause inflammation, such as pneumonia, all of which may influence baseline leukocyte counts. Finally, as a single-center retrospective study, selection bias was inevitable; therefore, prospective studies are needed to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal time point needs to be explored. Second, our study lacked some information at the time of participants' blood sample collection, including indicators of the acute inflammatory state (i.e., CRP, IL-1, IL-6, and TNF- α ) [ 29 31 ], some other drugs use such as the use of steroids and nonsteroidal anti-inflammatory drugs, previous use of antibiotics and therapy durations, and information about other diseases that could cause inflammation, such as pneumonia, all of which may influence baseline leukocyte counts. Finally, as a single-center retrospective study, selection bias was inevitable; therefore, prospective studies are needed to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, a recent meta‐analysis confirmed a link between TNF‐α polymorphism as well as circulating TNF‐α levels with ischemic stroke. 15 Although this finding seems plausible in light of the overwhelming evidence on inflammation and atherosclerosis, 16 further confirmatory studies are certainly needed before clinical relevance can be considered in regard to diagnosis of ischemic stroke causes.…”
Section: Discussionmentioning
confidence: 98%
“…In the past few years, tumor necrosis factor-α (TNF-α) has become a potential marker of stroke due to its essential role in stroke (Xue et al, 2022). Duan et al (2022) found that the increase in TNF-α level was related to the etiology of ischemic stroke, and TNF-α level was significantly correlated with the pathogenesis of ischemic stroke. All the above studies indicated that the therapeutic effect of quercetin, kaempferol, β-sitosterol, and the critical components of HGWD might be reflected in inflammationrelated signaling pathways and targets, which can effectively inhibit inflammation and play a role in the treatment of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%